Selective estrogen receptor modulators (SERM): A new choice for postmenopausal women and physicians who worry on cancer (Medical Journal of Indonesia, 2001)
The postmenopausal state is characterized by the cessation of menstruation, loss of ovarian function, and a dramatic decrease in the level of circulating estrogen. This state of estrogen deficiency contributes to the acceleration of several age-related health problems in women, including cardiovascular disease, osteoporosis, and dementia. Estrogen replacement is clearly effective in the short-term and long-term treatment and prevention of postmenopausal symptoms. However, until now, the amount of HRT user is still very low. Fear of breast cancer and endometrial cancer are the most common concern in using hormone replacement therapy (HRT), although the relationship between long-term HRT and breast cancer remains controversial. For physicians or patients, who worry on cancer, the ideal drug is now available i.e. the selective estrogen receptor modulators (SERM), with the generic name raloxifine. (Med J Indones 2001; 10: 187-90)